The art museum and the public library under a single roof: A nineteenth-century ideal pursued at the Toronto Public Library from 1883 to World War I - Williamson, Mary (Ontario History)

(untitled) (The Ontario Historical Society, 2006)
When in 1883 James Bain became the first chief librarian of the Toronto Public Library he was a fervent subscriber to the growing international enthusiasm for the integration of public libraries, art galleries and museums under one roof. It was said that these institutions belonged to all citizens and not just to an elite, and that they shared cultural aims that could be accomplished if their inter-dependency were recognized. While various obstacles – not the least was funding – prevented Bain from achieving this ideal in Toronto, under his leadership the Toronto Public Library became a major player in the art life of the city as a venue for exhibitions by individual artists and artists’ societies, and by acquiring thousands of works of art through donation and purchase. In the early 1900s all over Ontario, art lovers encouraged their fellow citizens to take advantage of art exhibitions and purchase opportunities in the public libraries, and to become involved in the creation and growth of library art collections.